2011
DOI: 10.1186/cc10035
|View full text |Cite
|
Sign up to set email alerts
|

Postresuscitation care with mild therapeutic hypothermia and coronary intervention after out-of-hospital cardiopulmonary resuscitation: a prospective registry analysis

Abstract: IntroductionMild therapeutic hypothermia (MTH) has been shown to result in better neurological outcome after cardiopulmonary resuscitation. Percutaneous coronary intervention (PCI) may also be beneficial in patients after out-of-hospital cardiac arrest (OHCA).MethodsA selected cohort study of 2,973 prospectively documented adult OHCA patients within the German Resuscitation Registry between 2004 and 2010. Data were analyzed by backwards stepwise binary logistic regression to identify the impact of MTH and PCI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
3
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 40 publications
2
53
3
5
Order By: Relevance
“…5 In addition, results from observational studies have suggested that some interventions, such as immediate coronary intervention, may improve survival in certain populations. 6,7 Over the past decade, the highest level of evidence for a treatment that improves outcomes came from 2 randomized trials published in 2002 that showed that induced hypothermia reduces mortality and improves neurological outcomes in patients with out-of-hospital ventricular fibrillation cardiac arrest. 8,9 Primarily on the basis of these trials, therapeutic hypothermia (TH) is now considered standard-of-care in the United States for patients who remain comatose after resuscitation for this particular patient population.…”
mentioning
confidence: 99%
“…5 In addition, results from observational studies have suggested that some interventions, such as immediate coronary intervention, may improve survival in certain populations. 6,7 Over the past decade, the highest level of evidence for a treatment that improves outcomes came from 2 randomized trials published in 2002 that showed that induced hypothermia reduces mortality and improves neurological outcomes in patients with out-of-hospital ventricular fibrillation cardiac arrest. 8,9 Primarily on the basis of these trials, therapeutic hypothermia (TH) is now considered standard-of-care in the United States for patients who remain comatose after resuscitation for this particular patient population.…”
mentioning
confidence: 99%
“…(27) In contrast with urbanization, higher level of hospital care, such as in a medical center, was associated with successful ROSC in our report. Several studies have identified in-hospital factors associated with improved mortality after successful resuscitation from OHCA in patients ad- (36,37) or with no ST elevation on ECG. (38,39) The benefit of ECMO on survival and neurological function in a selected patient group following OHCA had also been documented.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the hypothermia group demonstrated a significant reduction in infarct size as measured by cardiac magnetic resonance imaging and cardiac biomarker measurement. Gräsner et al 134 recently published work on the effect of PCI and TH in OHCA patients who survived to hospital admission. Patients who received TH without PCI demonstrated improved 24-hour survival and neurological outcome.…”
Section: Critical Interventionsmentioning
confidence: 99%